USING INSTAGRAM REELS TO INCREASE SPEAKING SKILL IN PROMOTION OF TOURSIM BY YOUTH OF COMMUINTY (KARANG TARUNA) TELAGABIRU - Hamzah, Amir (Universitas Samudra, 2024)
In Indonesia, many influencers use English to build their personal brand on social media such as Facebook or Instagram, and this condition is great opportunities to promote the wonderful Indonesia using social media such as Instagram Reels, and this condition was created in Tanjungbumi under - district, youth community (Karang Taruna).